Historical Analysis of Hunting in Turkestan at the End of the XIX – Beginning of the XX Century - Yusufaliev Shahzodjon Zafar oglu (Journal of Innovation in Education and Social Research, 2025)
This article examines the history and conditions of hunting in the Turkestan region at the end of the XIX – beginning of the XX century, based on periodical publications and archival sources.